The words of the semantic field of law according to the "Rules of Armenian Catholicos Hovhannes Mandakuni" - Barseghyan, Varduhi (Bulletin of Yerevan University B: Philology, 2024)
Hovhan Mandakuni holds a significant position in Armenian history during the 5th century. As a Catholicos, he not only dutifully serves his homeland but also leaves behind a remarkable literary legacy. Under his name, nine canons with ecclesiastical content are preserved, offering insights into the customs, laws, and corresponding punishments of the era’s church life. Analysis of these canons reveals that the vocabulary pertaining to law primarily comprises Iranian borrowings, alongside a notable presence of words derived from native Indo-European roots, which continue to be relevant in modern Eastern Armenian. Hybrid formations are scarce, and phraseological Unit predominantly consist of verbs. Despite the concise nature of the original text, 32 words and phraseological units pertinent to the field of law have been identified and delineated.